INCREASING THE LIFETIME OF LI-ION BATTERIES AS PART OF SELF-MANUFACTURED TRACTION BATTERIES FOR PORTABLE ELECTRIC VEHICLES - Татарчук, Тетяна; Середенко, Кирил; Олексенко, Олександра (SWorldJournal, 2023)
During the work, the designs of traction batteries for portable electric transport were considered and analyzed. Serious flaws have been revealed that battery manufacturers carefully hide. The inability of balancing BMS boards to prevent long-term effects